ANALISIS HUKUM SISTEM PEMERINTAHAN DAERAH BERBASIS LOCAL WISDOM DALAM MEWUJUDKAN REFORMASI BIROKRASI DI KABUPATEN KULON PROGO - Dewi, Indah Kusuma; Sapardiyono, Sapardiyono; Hardin, Hardin; Ramadhan, Faais Mufaasir; Andara, Darojatun (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The general principles of good governance were originally part of unwritten law and constitute ethical values that must be adhered to by state administrators both at the center and in the regions. These principles come from ethical values that have developed in society and have long been practiced by local people. Therefore, it can be said that these values were developed based on local wisdom and developed in society. These values were developed in the Regional Government System with the aim of improving public services in the context of Bureaucratic Reform. The aim of this research is to find out the Local Wisdom-based Regional Government System in the Kulon Progo Regency Government, to find out the General Principles of Good Governance (AAUPB) which can be the basis for Bureaucratic Reform of the Local Wisdom-based Regional Government System in the Kulon Progo Regency Government. The research methods used are normative juridical and empirical juridical The results of the research show that the Government System in the Regional Government of Kulon Progo Regency is based on the Specialty of the Special Region of Yogyakarta as contained in Article 7 paragraph (2) of Law Number 13 of 2012 concerning the Specialty of the Special Region of Yogyakarta. However, implementation in Kulon Progo Regency only consists of 4 (pillars), namely DIY Regional Government institutions, culture, land and spatial planning. Regarding the pillars of procedures for filling positions, positions, duties and authority of the Governor and Deputy Governor, they are only implemented in the Yogyakarta Special Region Province. The Satriya Government Culture which was prepared based on the Regulation of the Governor of the Special Region of Yogyakarta Number 53 of 2014 concerning Guidelines for the Implementation of Government Culture and which is an implementation of the Javanese Hamemayu Hayuning Bawana philosophy so that government cultural values can be implemented in the personal selves of officials within the Kulon Progo Regency Government is an actualization General Principles of Good Government (AUPB)